Concordance among digital gene expression, microarrays, and qPCR when measuring differential expression of microRNAs. (March 2010) - Pradervand, Sylvain; Weber, Johann; Lemoine, Frédéric; Consales, Floriane; Paillusson, Alexandra; Dupasquier, Mélanie; Thomas, Jérôme; Richter, Hannes; Kaessmann, Henrik; Beaudoing, Emmanuel; Hagenbüchle, Otto; Harshman, Keith
Profiling microRNA (miRNA) expression is of widespread interest given the critical role of miRNAs in many cellular functions. Profiling can be achieved via hybridization-based (microarrays), sequencing-based, or amplification-based (quantitative reverse transcription-PCR, qPCR) technologies. Among these, microarrays face the significant challenge of accurately distinguishing between mature and immature miRNA forms, and different vendors have developed different methods to meet this challenge. Here we measure differential miRNA expression using the Affymetrix, Agilent, and Illumina microarray platforms, as well as qPCR (Applied Biosystems) and ultra high–throughput sequencing (Illumina). We show that the differential expression measurements are more divergent when the three types of microarrays are compared than when the Agilent microarray, qPCR, and sequencing technology measurements are compared, which exhibit a good overall concordance.